Basic Directions of Foreign Trade and Internal Co-operation of the Eurasian Economic Union Countries - PODBIRALINA, Galina (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The external economic model of the Eurasian Economic Union (EAEU) is constantly improved in order to achieve deep integration and maximize the economic benefits of its members both within the EAEU and with third countries. A combination of theoretical and quantitative analysis, systematization, comparison, and descriptive statistics has made it possible to identify the main trends in the development of Eurasian integration (creating a single market of production factors and digital space, comfortable conditions for doing business and full realization of human capital) and the factors affecting cooperation of the countries participating in the EAEU (the consequences of economic crises in Russia and other member countries; internal barriers, seizures and restrictions, growing protectionism in international trade and sectoral pressure on the economy of Russia being one of the largest in the union). The paper assesses the development of trade cooperation of the member countries. The main vectors of foreign trade of the member countries of the Eurasian Economic Union (the European Union, the countries of the Asia-Pacific) have been identified. An assessment of the prospects for foreign trade cooperation of the EAEU is made and the influence of this factor on the economic development of the countries participating in cooperation agreements is found.